Октябрьский ветер: роман (Аугуст Якобсон ; перевод с эстонского А. Соколова) - Якобсон Аугуст (1973)
Экземпляры: КХ (20240929) / Инвентарный номер: 560412 / Сис.шифр: С(Эст) / Авт.знак: Я 46 / ГРНТИ: 17.82 / ББК: 84